Intrapersonal characteristics of body-related guilt, shame, pride, and envy in Canadian adults. (March 2016) - Pila, Eva; Brunet, Jennifer; Crocker, Peter R.E.; Kowalski, Kent C.; Sabiston, Catherine M.
Highlights: Small differences in body self-conscious emotions by sex, age, and weight. Women report higher negative body-related self-conscious emotions than men. Middle-aged adults report highest negative emotions and lowest positive emotion. Negative emotions are highest in individuals who are overweight or obese. Abstract: This study examined differences in body-related shame, guilt, pride, and envy based on intrapersonal characteristics of sex, age, and weight status in 527 Canadian adults. Compared to men, women reported significantly higher shame and guilt contextualized to the body. No sex differences were observed for envy or pride. Middle-aged adults reported higher shame and lower pride compared with young adults, whereas no age differences were observed with body-related guilt. Meanwhile, shame and guilt were highest for individuals who had overweight or obese weight status, and pride was highest in individuals with average weight status. Overall, effect sizes were small and there were no significant interaction effects between sex, age, and weight status across body-related emotions. Further research is needed to capture similarities and differences of body-related self-conscious emotions between intrapersonal characteristics, to aid the development of intervention strategies to manage this important dimension of body image.